PERANAN KEBIJAKAN PUBLIK TERHADAP PEMBERANTASAN KORUPSI (KASUS UNINTERRUTIBLE POWER SUPLY PEMERINTAH DI DKI JAKARTA) - Isnawati, Isnawati (Universitas 17 Agustus 1945 Samarinda, 2017)
The objective of this research is to know the corruption on the uninterrutible power suply di DKI Jakarta in 2015 involving the members of Jakarta parliaments.The method of the it is library research taken from Gatra magazine published on August 2,2017.The results of the research are (1).The UPS project has been apointed to be involved the crime namely corruption,(2).The top director of PT.Offtarindo Adhiprima is involved in this project,(3).The corruption has been detected in 2015,(4).The innitial names of the legislators of the special region Jakarta MF and FZ and from the campany concerned are HL and PZ,(5).This case has been performed in Tipikor court state of Jakarta.The suggestions of the researcher are,(1).The antisipation and the control of the local government has to be maximized,(2).The payment of the project concered has to use electronic tools,(3).The acccused people has to be sentenced maximally,(4).The money being corrupted has to be payed by the accused people,(5). The acccused people has to be deleted from the personal staff.